Predictors of late presentation for HIV care among adults at AIDS Healthcare Foundation clinic in Matsapha, Manzini Region, Eswatini - Lomanono N. Ngidie; Ruth Wahila; Phadaless Sinkamba (International Journal of Africa Nursing Sciences)
Introduction: Patients presenting late for HIV care often experience poor health outcomes. The study aimed to establish predictors of late presentation for HIV care to enable formulation and institution of public health interventions that enhance early presentation for HIV care. Methods: This descriptive cross-sectional research study surveyed patients diagnosed with HIV but not yet enrolled into care. Inclusion criteria were: a patient with a current CD4 cell count result; aged 18 years and above; both male and female. SPSS version 27.0 was used to analyze data with descriptive statistics, Chi-square and regression analysis. Results: Data were obtained from a sample of 60 respondents. The age of respondents ranged from 18 – 62 years with a mean age of 35 years. More than half 33 (55 %) of the respondents were males. The prevalence of late presentation for HIV care was 76.7 %. Older age and unemployment were associated with late presentation to HIV care. Fear of stigma and discrimination status (p = 0.046) and poor healthcare practices were significantly associated with late presentation to HIV care (p = 0.007). Conclusions: The prevalence of late presentation for HIV care in Eswatini is high. To improve patients’ health outcomes, healthcare facilities should instil interventions to upscale early presentation for HIV care and lessen the burden of late presentation consequences on the healthcare system, the community and the patient.